PERSONALIZED COGNITIVE COUNSELING IN PREVENTING RISK BEHAVIOR AMONG MEN WHO HAVE SEX WITH MEN (MSM): A LITERATURE REVIEW - Lussy Afriyanti; Agung Waluyo (Alta Dharma Publisher, 2019)
The current trend of HIV infection shows an increase in cases among men who have sex with men (MSM). Risk behavior in MSM has shown a high prevalence of moderate and worrying risk behaviors for HIV infection, including unprotected anal intercourse (UAI) and drug use. This literature review aims to explore the effectiveness of Personalized Cognitive Counseling (PCC) interventions in reducing risk behaviors for HIV transmission to MSM. Articles discussed in this literature study were obtained from several databases using the keywords “personalized cognitive counseling,